Departments involved during the first episode of acute heart failure and subsequent emergency department revisits and rehospitalisations: an outlook through the NOVICA cohort. (7th August 2019) - Miró, Òscar; García Sarasola, Ana; Fuenzalida, Carolina; Calderón, Sofía; Jacob, Javier; Aguirre, Alfons; Wu, Da M.; Rizzi, Miguel A.; Malchair, Pierre; Haro, Antonio; Herrera, Sergio; Gil, Víctor; et al.
Abstract : Objectives: We investigated the natural history of patients after a first episode of acute heart failure (FEAHF) requiring emergency department (ED) consultation, focusing on: the frequency of ED visits and hospitalisations, departments admitting patients during the first and subsequent hospitalisations, and factors associated with difficult disease control. Methods and results: We included consecutive patients diagnosed with FEAHF (either with or without previous heart failure diagnosis) in four EDs during 5 months in three different time periods (2009, 2011, 2014). Diagnosis was adjudicated by local principal investigators. The clinical characteristics of the index event were prospectively recorded, and all post‐discharge ED visits and hospitalisations [related/unrelated to acute heart failure (AHF)], as well as departments involved in subsequent hospitalisations were retrospectively ascertained. 'Uncontrolled disease' during the first year after FEAHF was considered if patients were attended at ED (≥ 3 times) or hospitalised (≥ 2 times) for AHF or died. Overall, 505 patients with FEAHF were included and followed for a mean of 2.4 years. In‐hospital mortality was 7.5%. Among 467 patients discharged alive, 288 died [median survival 3.9 years, 95% confidence interval (CI) 3.5–4.4], 421 (90%) revisited the ED (2342 ED visits; 42.4% requiring hospitalisation, 34.0% AHF‐related) and 357 (77%) were hospitalised (1054 hospitalisations; 94.1% through ED, 51.4% AHF‐related). AHF‐related hospitalisations were mainly in internal medicine (28.0%), short‐stay unit (26.3%), cardiology (20.8%), and geriatrics (14.1%). Only 47.4% of AHF‐related hospitalisations were in the same department as the FEAHF, and internal medicine involvement significantly increased with subsequent hospitalisations ( P = 0.01). Uncontrolled disease was observed in 31% of patients, which was independently related to age > 80 years [odds ratio (OR) 1.80, 95% CI 1.17–2.77], systolic blood pressure < 110 mmHg at ED arrival (OR 2.61, 95% CI 1.26–5.38) and anaemia (OR 2.39, 95% CI 1.51–3.78). Conclusion: In the present aged cohort of AHF patients from Barcelona, Spain, the natural history after FEAHF showed different patterns of hospital department involvement. Advanced age, low systolic blood pressure and anaemia were factors related to uncontrolled disease during the year after debut.